DINAMIKA PEMBIAYAAN PASAR MODAL TERHADAP KEBERLANJUTAN USAHA AGRIBISNIS: KASUS UMKM KRIPIK DAHLIA - Hildayanti, Hildayanti; Hikmah, Aulia Nurul; Arfah, Aziza Noor Sheha; Sari, Putri Nurul; Nurfadilla, Nurfadilla Nurul; Salsabila, Salsabila Sheha; Asmiranda, Asmiranda Sheha (Jurnal Riset Multidisiplin Agrisosco, 2025)
Capital market financing is one of the alternatives that can improve access to capital for micro, small and medium enterprises (MSMEs) in the agribusiness sector. This study aims to analyze the effect of capital market financing on agribusiness sustainability, focusing on the case study of Kripik Dahlia MSMEs. Kripik Dahlia is an MSME engaged in the production of processed bananas, corn, pineapple, cassava chips etc. and has utilized financing from the capital market to develop its business. Using a qualitative method with a case study approach. The results showed that capital market financing helped Kripik Dahlia increase production capacity, diversify products, and expand market reach, both locally and internationally. However, they face obstacles such as limited knowledge, administrative difficulties, and lack of support from financial institutions. In conclusion, capital market financing provides great opportunities for MSMEs to grow. Education, simplification of administrative processes, and better support from financial institutions are needed to maximize the benefits of this financing for MSMEs.